Understanding Depression in People Living with Multiple Sclerosis: A Narrative Review of Recent Literature - Amy B. Sullivan; Bryan Davis; Julie Kidd; Horacio Chiong-Rivero (Neurology and Therapy)
Abstract Multiple sclerosis (MS) is a chronic neurodegenerative and autoimmune disease that affects approximately 1 million adults in the US. Psychologic disorders are typical comorbidities in people with MS (pwMS), with depression being the most common. Clinical depression in pwMS can substantially impact quality of life and factor heavily in treatment adherence. Depression can surface early in MS, becoming more prevalent as the disease progresses and the severity of clinical disability increases. The etiology of comorbid depression in pwMS is not completely understood, but recent research has indicated that structural and functional brain abnormalities, along with genetic and immunologic factors, may contribute to the pathogenesis of depression in pwMS. Although depression has a significant impact on pwMS, it is often underdiagnosed and undertreated. Furthermore, the efficacy of pharmacologic and non-pharmacologic approaches for treating depression in pwMS has not been thoroughly investigated, with most studies showing minimal or no beneficial effect. Improved evaluation and diagnosis of depression and a better understanding of its pathophysiology may provide a stronger foundation for treatment and management of pwMS suffering from depression. This review discusses recent research on the potential causes of depression, the risk factors associated with developing depression, and the overall impact of depression in pwMS. It also reviews patient-reported outcomes utilized to assess depression in pwMS and the impact of disease-modifying therapies on depression in pwMS. Consideration is also given to management of depression in pwMS (both pharmacologic and non-pharmacologic) to better facilitate the patient journey.